First record of Denticollis borealis (Paykull, 1800) (Coleoptera, Elateridae) from Kazakhstan - Temreshev, Izbasar I. (Acta Biologica Sibirica, 2025)
Denticollis borealis (Paykull, 1800) (Coleoptera: Elateridae) is recorded for the first time in Kazakhstan. Species was found in bracket fungus and under bark, in galleries of larvae of Upis ceramboides (Linnaeus, 1758) and Sinodendron cylindricum (Linnaeus, 1758). It is possible that the larvae of D. borealis are predators of the species of beetles in whose galleries it was found. A key to the known species of the genus Denticollis from Kazakhstan is also given.